The Development of Science Learning Media Using Android Applications in Solar System Subject - Riris Apriliana; Murfiah Dewi Wulandari (Jurnal Basicedu, 2022)
This research uses the R&D (Research and Development). The model used in this research is ADDIE (Analysis, Design, Development, Implementation, and Evaluation), but researcher only limit it to the development stage. This study aims to produce and test the feasibility of Android-based science learning media in solar system subjects, especially in the sixth-grade. Data collection techniques used are literature studies and questionnaires/questionnaires. The product feasibility test is carried out by media experts and material experts. The data analysis technique was carried out qualitatively and quantitatively. Based on the feasibility test conducted by the experts, it can be seen that the validation results by media experts obtained an average of 4.69 so it indicated the "Very Worthy" category, then the validation results by material experts obtained an average of 4.32 so it entered in the “Very Worthy” category. Based on these data, it can be concluded that the Android application-based science learning media in the solar system subject is appropriate to be used as a medium for learning science, especially the solar system subject.